放棄人類胚胎“14天限制” 的倫理反駁: An Argument against the Abandonment of the 14-day Limit on Human Embryo Research - ZHANG, Xinqing (International Journal of Chinese & Comparative Philosophy of Medicine, 2021)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. This article explores prominent arguments in favor of and against extending the current 14-day statutory limit on the maintenance of human embryos. I discuss the history of the 14-day limit and the reasons behind the decision to opt for a compromise between competing moral views. I then argue that the ISSCR's guidelines for extending the 14-day limit are not a valuable tool, despite their potential to contribute scientific knowledge. The importance of respecting the 14-day rule should be acknowledged by ethics committees in the current research ethics climate of mainland China.